Experimental investigation of an autonomous liquid-cooled uninterruptible power supply (UPS) - Hnayno, Mohamad; Chehade, Ali; Klaba, Henryk; Bauduin, Hadrien; Polidori, Guillaume; Maalouf, Chadi (Energy Reports, 2023)
This paper presents a new liquid-cooling technology for uninterruptible power supply (UPS) units in which an air-cooling system is combined with an indirect water-cooling system based on direct-chip cooling. This cooling architecture provides more opportunities to use free cooling as the main or only cooling system for optimal data centres (DCs). An experimental investigation was conducted using a 600 kW SOCOMEC UPS to identify the thermal behaviour of the system. Five thermal hydraulic tests were conducted under different thermal conditions, flow rates, and room temperatures. A 20 K temperature difference profile was validated with a safe operation of all UPS electronic equipment with a water flow rate of 13 l/min and inlet water and air room temperatures of 32 and 40 °C, respectively, resulting in a thermal efficiency of 82.27%. The experiments suggest that a DC-facility water-inlet temperature up to 41 °C is acceptable for UPS units. The effects of decreasing the water flow rate and increasing the water and air room temperatures were also analysed. A decrease in inlet water and air temperatures from 41 °C to 32 °C and from 47 °C to 40 °C, respectively, increased the thermal efficiency by 8.64%. A decrease in water flow rate from 20 l/min to 13 l/min reduced the thermal efficiency by 7.7%. Furthermore, an energy performance analysis comparison was performed between air- and water-cooled UPS units at both the UPS and infrastructure levels. A case study of a 600 kW UPS in a data centre in Roubaix, north of France, was investigated. The liquid-cooled UPS reduced the total annual energy consumption of the cooling system by at least 85% compared with an air-cooled UPS.
Keywords: Data centre; Experiment; Heat transfer; Liquid cooling; Uninterruptible power supply unit cooling